2021
DOI: 10.2196/30268
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of an mHealth App for Youth With Substance Use and Mental Health Needs: Iterative, Mixed Methods Design

Abstract: Background Treating substance use disorders (SUDs) during adolescence can prevent adult addiction and improve youth outcomes. However, it can be challenging to keep adolescents with SUDs engaged in ongoing services, thus limiting potential benefits. Developmentally appropriate tools are needed to improve treatment engagement during and between sessions for youth with SUDs and mental health disorders. Mobile health apps may augment or replace psychotherapy components; however, few have been develope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Findings from this study also represent cross-cutting themes that may be useful for research and practice involving additional health behaviors (e.g., drinking, smoking, vaping). Indeed, adolescent researchers focused on substance use (Adams et al, 2021) as well as alcohol use and suicidal behavior (O'Brien et al, 2019) reported similar findings regarding the desire for a mobile application to provide health information and social support among adolescents. Finally, findings regarding peer learning are echoed in previous research.…”
Section: Discussionmentioning
confidence: 80%
“…Findings from this study also represent cross-cutting themes that may be useful for research and practice involving additional health behaviors (e.g., drinking, smoking, vaping). Indeed, adolescent researchers focused on substance use (Adams et al, 2021) as well as alcohol use and suicidal behavior (O'Brien et al, 2019) reported similar findings regarding the desire for a mobile application to provide health information and social support among adolescents. Finally, findings regarding peer learning are echoed in previous research.…”
Section: Discussionmentioning
confidence: 80%
“…All other apps did not specify how the app should be used. Thirty-three percent of apps used gamification elements to motivate patients to use the app ( 55 , 58 , 62 , 64 , 73 , 76 , 77 , 79 ). Two apps used chatbots in their program to provide patients with personalized treatment ( 55 , 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to apps for treating depression and anxiety, adolescent patients believe that the apps have good usability and ease of use and can encourage them to share their thoughts, feelings, and behavioral information more openly and honestly while protecting their privacy ( Adams et al, 2021 ). However, due to the severe condition of patients with mental illness, the apps not only are used independently by patients but also serves as a bridge between therapists and patients.…”
Section: Resultsmentioning
confidence: 99%